Weaving Sustainability into Affordable Housing : Anna Builders - Indira, A.; Tholath, Deepa Ittimani (AMC Indian Journal of Entrepreneurship, 2019)
Anna Builders has been building affordable housing units since 2000. Founded by Mr. Venu, who is taking forward his late father’s vision of housing for all, Anna Builders has till now handed over 30,000 sq. m. of built up space aimed at the first time buyer and user. Mr. Venu had recently attended a seminar organized by CII and the Indian Green Building Council (IGBC) to educate small and medium builders regarding the benefits of building with eco-friendly materials which had got him thinking. The case traces his dilemma in striking a balance in the affordable housing sector between the green building norms and the base line profits of the company. Will he be able to do it?